Predictive Value of Serum Cholic Acid and Lithocholic Acid for the Diagnosis in an Intrahepatic Cholestasis of Pregnancy Population with High Levels of Total Bile Acids and the Correlation with Placental Hypoxia-Inducible Factor-1α - Cheng CY; Zeng GY; Wang T; Su YH; Xu FD; Luo H; Zhong HT; Chen XL (Dove Medical Press, 2022)
Chu-Yun Cheng,1 Guan-Yin Zeng,1 Tong Wang,1 Yan-Hua Su,1 Feng-Dan Xu,2 Hong Luo,1 Hui-Ting Zhong,1 Xiu-Lan Chen1 1Department of Obstetrics, Dongguan Eighth People's Hospital (Dongguan Children's Hospital), Dongguan, Guangdong, 523325, People's Republic of China; 2Department of Neonatal Clinic, Dongguan Eighth People's Hospital (Dongguan Children's Hospital), Dongguan, Guangdong, 523325, People's Republic of ChinaCorrespondence: Chu-Yun Cheng, Department of Obstetrics, Dongguan Eighth People's Hospital (Dongguan children's Hospital), No. 68, West Lake 3rd Road, Shilong Town, Dongguan, Guangdong, 523325, People's Republic of China, Tel +86 13688988412, Email chChu-Yun@126.comObjective: This study aimed to investigate the ability of serum cholic acid (CA) and lithocholic acid (LCA) in the diagnosis and perinatal prognosis assessment of intrahepatic cholestasis of pregnancy (ICP), and the relationship between both indicators and hypoxia-inducible factor-1α (HIF-1α).Methods: Between March 2020 and March 2021, pregnant women with high levels of total bile acid (TBA) in the late pregnancy with TBA ≥ 10 μmol/L and TBA < 10 μmol/L (control group) were included for the retrospective study. Those with TBA ≥ 10 μmol/L were divided into the ICP group and the asymptomatic hypercholanaemia of pregnancy (AHP) group based on ICP symptoms. The comparison of the bile acid profiles, the receiver operating characteristic (ROC) curve analysis, and Pearson correlation analysis were conducted successively.Results: Nine types of bile acids were significantly higher in ICP and AHP than in the control group, while CA and LCA serum levels in the AHP group were significantly lower than those in the ICP group (P < 0.05). The ROC curve analysis showed that LCA, CA, and LCA+CA were all diagnostic indicators for ICP, and LCA+CA displayed the greatest diagnostic value (area under the curve (AUC), 0.923). Subgroup analysis using the LCA+CA cut-off point (3.28 μmol/L) as the subgroup indicator proved that the incidence of adverse perinatal outcomes and the placental HIF-1α positivity were significantly higher in the high LCA+CA group than in the low LCA+CA group (P < 0.05). Pearson correlation analysis revealed significant positive correlations of HIF-1α expression levels to LCA, CA and LCA+CA (r = 0.473, 0.537, 0.619, respectively. P < 0.05 in all).Conclusion: This study confirmed that CA and LCA have a predictive diagnostic value for ICP in pregnant women, and the combined evaluation is associated with adverse perinatal outcomes, and LCA+CA positively correlates to placental HIF-1α expression levels.Keywords: cholic acid, lithocholic acid, intrahepatic cholestasis of pregnancy, hypoxia-inducible factor-1&#x03B1